Housing as a starting point for migrants' integration: opportunities and obstacles in Emilia-Romagna region - Marta Salinaro; Marta Ilardo (University of Bologna, 2022)
The article focuses on the need to implement housing integration practices for migrants in Italy. Through an overview of the literature on housing, with an insight at the Emilia-Romagna region, the aim was to identify opportunities and obstacles that arise for refugees and holders of international protection once they leave the reception and integration services. As part of the H2020 MERGING project we introduce a first phase of the qualitative research conducted and the methodology adopted for the selection of the case study investigated. The selected project presents itself as a potential model to be implemented to address the housing issue as a right to be protected but also as a starting point for the integration process.